Pengembangan Usaha Pengrajin Tapis Lampung Terhadap Peningkatan Pendapatan Karyawan Dalam Perspektif Ekonomi Islam: Studi pada Pengrajin Tapis, Nurbaiti Tapis Jaya, Desa Negeri Ulangan Jaya, Kec. Negeri Katon, Kab. Pesawaran - Fitri Delia Nur Imani; M. Yusuf Bachtiar; Okta Supriyaningsih (ITB AAS INDONESIA Surakarta, 2026)
This research is based on the great potential of the Tapis Lampung handicraft business as a creative industry with cultural and economic value for increasing artisans' income. Therefore, business development still faces various obstacles, including suboptimal digital marketing, limited business management, and unstable employee income. The purpose of this research is to analyze the business development of MSME Tapis Jaya and its impact on increasing employee income from the perspective of Islamic economics. The research method used is qualitative field research, and data are collected through observation, interviews, and documentation with business owners and Tapis Jaya artisans. The results of his research show that business development is achieved through product innovation, improved production quality, the use of social media for promotion, and expanded marketing networks. This has a positive impact on employee income, even though it is not optimal due to limited digital technology and market competition. From the perspective of Islamic economics, business development reflects the principles of honesty, justice, responsibility, and appropriate wages.